Does government size affect per-capita income growth? A Hierarchical meta-regression analysis - Sefa Awaworyi Churchill; Siew Ling Yew; Mehmet Ugur (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We conduct a hierarchical meta-regression analysis to review 87 empirical studies that report 769 estimates for the effects of government size on economic growth. We follow best-practice recommendations for meta-analysis of economics research, and address issues of publication selection bias and heterogeneity. When size is measured as the ratio of total government expenditures to GDP, the partial correlation between government size and per-capita GDP growth is negative in developed countries, but insignificant in developing countries. When size is measured as the ratio of consumption expenditures to GDP, the partial correlation is negative in both developed and developing countries, but the effect in developing countries is less adverse. We also report that government size is associated with less adverse effects when primary studies control for endogeneity and are published in journals and more recently, but it is associated with more adverse effects when primary studies use cross-section data. Our findings indicate that the relationship between government size and per-capita GDP growth is context-specific and likely to be biased due to endogeneity between the level of per-capita income and government expenditures.
Additional information: This paper synthesize the evidence on the relationship between government size and growth, using a hierarchical meta-regression model. It provides a systematic assessment of the literature and offers some insights into the heterogeneity of the existing findings.
Keywords: O40; H50; C1; 330; Economic growth; Government size; Government expenditures; Government consumption; Meta-analysis; Evidence synthesis